2017
DOI: 10.22623/ijapsa.2017.3010.fkl6w
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of import demand of rice in Uganda

Abstract: Rice has been singled out as one of the crops that play an important role as both food and a cash crop in Uganda. Its importance has become more critical due to increasing demand. The increased demand has created a gap in domestic supply which has to be covered through imports. This study analyses determinants of import demand for rice in Uganda using econometric methods. Population, domestic rice production, own price and own consumption were found to be significant and therefore influencing rice imports in U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
3
5
0
Order By: Relevance
“…The negative sign suggests that a 1% increase in GDP could result in about a 1.59% decrease in the quantity of imported sago starch. This result is similar to a study in Malaysia where economic growth has a negative relationship with imports (Sulaiman and Saad 2009) but contrary to the result of Hyuha et al (2017). The situation where income increases, but demand decreases could happen when the good is inferior.…”
Section: Determinants Of Import Demand For Sago Starch In Japansupporting
confidence: 85%
See 1 more Smart Citation
“…The negative sign suggests that a 1% increase in GDP could result in about a 1.59% decrease in the quantity of imported sago starch. This result is similar to a study in Malaysia where economic growth has a negative relationship with imports (Sulaiman and Saad 2009) but contrary to the result of Hyuha et al (2017). The situation where income increases, but demand decreases could happen when the good is inferior.…”
Section: Determinants Of Import Demand For Sago Starch In Japansupporting
confidence: 85%
“…A double-logarithmic linear function is applied for modeling and determine the demand functions in this paper. Several studies revealed that a double-logarithmic linear function was favored in import demand analysis models, such as import demand for meat (Goktolga 2006), import demand for dairy products (Karkacier 2000), import demand for vegetable oil and products (Kizilaslan and Kizilaslan 2006), import demand for wheat (Baiyegunhi and Sikhosana 2012;Uzunoz and Akcay 2009) and import demand for rice in Uganda (Hyuha et al 2017). In addition, the double log specification is used to examine the Japan's horticultural import performance.…”
Section: Model Specificationmentioning
confidence: 99%
“…On the same vein, using double logarithmic model and time series data spanning from 1961 to 2013, Hyuha et al (2017) analysed the determinants of rice import demand in Uganda. With the study aimed at ascertaining the key parameters influencing rice import demand, the regression results revealed that domestic rice production, population and own rice consumption significantly influenced rice import demand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, an appreciation of Kenya shillings against a foreign currency is anticipated to have a positive effect on maize imports. The use of this variable as an explanatory variable is justified by past empirical studies (e.g., Hyuha et al, 2017).…”
Section: Description Of Variablesmentioning
confidence: 99%
“…The food and beverage industry directly impacts the daily lives of the entire society and plays a vital role in both regional and global economies (Zhu et al, 2018). Supply chain risks are analysed by most scientists (Xu et al, 2020;Khanal, 2018;Cimprich et al, 2017;Kolotzek et al, 2018;Hyuha et al, 2017;Bakumenko, 2019;Baryannis et al, 2019). The structure of agri-food supply chains is becoming increasingly complex, making them more sensitive to different societal levels and risks.…”
Section: Literature Reviewmentioning
confidence: 99%